Kapasitas Kelembagaan dalam Pengembangan Arboretum Gambut Sungai Pakning Kabupaten Bengkalis - Miftahul Jannah; Zulkarnaini Zulkarnaini (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
This research was conducted because Sungai Pakning sub-district, Bengkalis Regency, was one of the areas that experienced land and forest fires that occurred in Riau Province in 2015. So far, peatland management has often failed both by the government and companies. One of the failures is that they only focus on restoring land and neglect community empowerment. With the independent peat village program created by PT. Pertamina RU II Production, Sungai Pakning, Bengkalis Regency. Among the self-sustaining peat village programs, there is an environmental conservation program that has become the center of attention for environmentalists, namely the development of peat forest into a peat arboretum. This study aims to determine the institutional capacity in the development of the peat arboretum and to find out what are the supporting factors for institutional capacity in the development of the peat arboretum in Sungai Pakning, Bengkalis Regency. This research was conducted using a qualitative descriptive method. Data obtained through interviews and field observations. The results of this study indicate that the institutional capacity measure according to Damanik and Weber has shown good capacity in the aspects of leadership and coordination, aspects of external partnerships, aspects of potential development, and aspects of promotion. In a good institutional capacity supported by 1) facilities and infrastructure, which is carried out continuously, 2) good cooperation between various parties or institutions involved in the development of the peat arboretum.